Improving participatory community communication on halal tourism in Banten province using social evolution model - Syifa Mutiara Ummah; Tantan Hermansyah; Nasichah Nasichah (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — Halal tourism has become a trending destination for the people of Indonesia, including the province of Banten, which has religious characteristics, varied types of tourism, an abundance of Islamic boarding schools, and a majority Muslim population. Low community participation communication causes obstacles to halal tourism destinations. The research aims to reduce barriers to halal tourism through participatory communication communities in Banten province with a social evolution approach.Method — The research uses qualitative methods with a grounded theory approach. Determination of the sample using purposive sampling, while the data source is obtained from interviews, literature, and documentation. Data analysis uses design thinking with triangulation techniques.Result — The research found that increasing halal tourism required participatory community communication with a social evolution approach, including increasing education on halal certification and LPPOM-MUI, building public awareness about halal tourism, and community involvement in halal tourism. The design thinking approach formulates solutions to improve participatory communication of the community regarding halal tourism through optimizing halal certification bodies, MUI, religious and social institutions, providing halal tourism awareness training, providing information and technology training, providing support for licensing, having effective social media, marketing, safety, and comfort due diligence, permits and certification, increasing halal tourism marketing, improving the safety and comfort. The research implies that higher participation in public communication towards halal tourism will reduce local governments' obstacles.Contribution — Research contributes to increasing the Banten community’s participation in halal tourism. The local government will support regulations and facilitate reducing obstacles to halal tourism.